Poetic Image as Central Element in Early Imagist Poetry - Fariha, Inayatul (Journal of English and Education (JEE), 2009)
At the beginning of 20th century, the imagists, consisting of a group of Anglo-American poets with Ezra Pound as the leading figure emerged. This group of poets posed an attack on every aspect of romanticism. This group encouraged the use of experimental form in poetry and promoting the 'verse libre' poetic technique they recognized the use of traditional form in Thomas Hardy's poem that break away from the 'sentimental optimism and nostalgia of Romantics and symbolist, giving the poems 'a modernistic clarity of vision' (Williams, 1946, p. 17). As the name suggest, the image become the central element in the imagist poetry. The main point of imagism itself centers on the 'image' itself, clearly stated by the poets' to recreate an otherwise inexpressible and unique experience of the insight" (William, 1946,p.18and Hughes, 1960,p.43) This essay discusses the role of poetic images in the works of early imagist poets. The discussion covers the analysis on the poems written by Ezra Pound, H.D., Richard Aldington and William Carlos Williams with the focus how the images function in the selected poems.At the beginning of 20th century, the imagists, consisting of a group of Anglo-American poets with Ezra Pound as the leading figure emerged. This group of poets posed an attack on every aspect of romanticism. This group encouraged the use of experimental form in poetry and promoting the 'verse libre' poetic technique they recognized the use of traditional form in Thomas Hardy's poem that break away from the 'sentimental optimism and nostalgia of Romantics and symbolist, giving the poems 'a modernistic clarity of vision' (Williams, 1946, p. 17). As the name suggest, the image become the central element in the imagist poetry. The main point of imagism itself centers on the 'image' itself, clearly stated by the poets' to recreate an otherwise inexpressible and unique experience of the insight" (William, 1946,p.18and Hughes, 1960,p.43) This essay discusses the role of poetic images in the works of early imagist poets. The discussion covers the analysis on the poems written by Ezra Pound, H.D., Richard Aldington and William Carlos Williams with the focus how the images function in the selected poems.